2021
DOI: 10.3390/jcm10112244
|View full text |Cite
|
Sign up to set email alerts
|

Non-Selective Beta-Blockers Decrease Infection, Acute Kidney Injury Episodes, and Ameliorate Sarcopenic Changes in Patients with Cirrhosis: A Propensity-Score Matching Tertiary-Center Cohort Study

Abstract: Background: Cirrhotic complications resulting from portal hypertension can be considerably reduced by non-selective beta-blockers (NSBBs); however, scarce studies have investigated therapeutic agents for other complications. We aimed to investigate the effects of NSBBs on common cirrhotic complications of infection, acute kidney injury (AKI), chronic renal function declination, and sarcopenic changes. Methods: Medical records of hospitalization for cirrhosis with at least a 4-year follow-up were analyzed and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…However, Li et al showed that the administration of NSBBs may reduce the occurrence of AKI and marginally alleviate chronic renal function declination [52]. Maiwall et al observed consecutive cirrhotic patients with a complete record of baseline hemodynamics.…”
Section: Nsbbs and Renal Dysfunctionmentioning
confidence: 99%
“…However, Li et al showed that the administration of NSBBs may reduce the occurrence of AKI and marginally alleviate chronic renal function declination [52]. Maiwall et al observed consecutive cirrhotic patients with a complete record of baseline hemodynamics.…”
Section: Nsbbs and Renal Dysfunctionmentioning
confidence: 99%
“…A retrospective study by Li et al compared 20 cirrhotic patients treated with NSBBs with 20 propensity-score matched cirrhotic patients not on NSBBs who had abdominal CTs after 4 years of follow up. The cirrhotic patients who did not receive NSBBs had a significantly reduced skeletal muscle index at 4 years (mean SMI alteration −1.782 ± 4.624 cm 2 /m 2 ) compared with patients who did receive NSBBs (mean alteration 1.195 ± 5.633 cm 2 /m 2 ) [ 139 ]. Further, ideally, prospective studies are needed to clarify the effect of NSBBs on malnutrition and sarcopenia in patients with cirrhosis and portal hypertension.…”
Section: Treatment Of Portal Hypertensionmentioning
confidence: 99%
“…Beta blockers have been suggested as a possible external factor contributing to malnutrition in cirrhosis. However, a recent study found that patients who received non-selective beta blockers had actually better skeletal muscle index and improvement in sarcopenia[ 22 ].…”
Section: Pathogenesismentioning
confidence: 99%